MENELISIK KINERJA KEUANGAN PEMERINTAH KOTA DI PROVINSI JAWA TENGAH - Syafnita Syafnita (Fakultas Ekonomi Universitas Pekalongan, 2021)
This research aims to analyze financial performance which consists of the Independence Ratio, Effectiveness Ratio, Activity Ratio, and Debt Ratio in municipal governments in Central Java Province for the period 2015-2019. This research uses descriptive analysis method to determine the development of financial performance from year to year. The results of this study indicate that the average performance of the independence ratio is around 39.01% - 46.18% which is included in the low criteria. for the average effectiveness ratio ranged from 99.06% - 109.40% in very effective criteria. And for the calculation of all activity ratios are less than 50%, including the bad criteria because the ratio ranges from 19.11% - 25.38%. The last of the debt ratio is included in the criteria for high loan repayment capacity with the calculation of the average ratio from year to year ranging from 1.52% - 2.23%, its mean that all cities have high capabilities. the financial performance of city governments in Central Java Province atgenerally good, even though it is in poor criteria, there is an increase in financial performance improvements during this research period.